Cofiring of LTCC multilayer assemblies with integrated NTC thermistor temperature sensor layers. Issue 19 (1st October 2021) - Reimann, Timmy; Barth, Stefan; Capraro, Beate; Bartsch, Heike; Töpfer, Jörg
Abstract: We have studied the integration of Ni–Co–Zn–Mn spinel NTC thermistor layers into LTCC multilayer modules. Sintering of the cubic spinel Ni0.5 Co0.5 Zn0.75 Mn1.25 O4 with addition of 3 wt% Bi2 O3 additive at 900 °C resulted in samples with 96% density and with good electrical performance. Thermistor spinel tapes, fabricated using doctor blade tape casting, were stacked with layers of a commercially available low-k dielectric LTCC tape, and cofired at 900 °C. Free or constrained cofiring did not give crack-free multilayer samples. Thermistor layers were then integrated combining the commercial LTCC tape with a Zn titanate-based tape in one multilayer laminate, and error-free multilayer samples with a room-temperature resistivity of ρ298 = (2, 9 ± 0.08) kΩcm and a thermistor constant of B = (4280 ± 200) K were obtained. This demonstrates the possibility of cofiring of functional ceramic and low-k LTCC tapes and shows the potential of NTC spinel thermistor layers as temperature sensors integrated in complex LTCC multilayer architectures.